Meaning and components of quality of life among individuals with spinal cord injury in Yogyakarta Province, Indonesia. Issue 10 (8th May 2018) - Ferdiana, Astri; Post, Marcel W. M.; King, Nigel; Bültmann, Ute; van der Klink, Jac J. L.
Abstract: Purpose: Knowledge on the meaning of quality of life in individuals with spinal cord injury in developing countries is limited. This study aims to explore the meaning and components of quality of life for individuals with spinal cord injury in a rural area in Indonesia. Method: Data were obtained through semi-structured interviews with 12 individuals with paraplegia (8 males, 4 females) aged 24–67 years. Thematic analysis was used to identify themes that constitute meaning and components of quality of life. Results: Quality of life was not an easily understood concept, while "life satisfaction" and "happiness" were. Life satisfaction was associated with a person's feeling when achieving goals or dreams and related to fulfillment of needs. Thirteen components of life satisfaction were identified and categorized into five domains as follows: (1) participation: earning income and work, being useful to others, community participation, and having skills and knowledge, (2) social support: social support, social relationship, (3) relationship with God: injury is God's will, praying, (4) independence: being independent, mobility and accessibility, and health, and (5) psychological resources: accepting the condition, maintaining goals and motivation. Conclusions: Social, cultural and religious influences were prominent in the perception of life satisfaction. The measurement of quality of life for individuals with spinal cord injury in Indonesia needs to consider locally perceived meaning and components of quality of life. Implications for Rehabilitation: Financial, social and health needs of individuals with spinal cord injury in Indonesia must be immediately addressed. To increase financial independence, rehabilitation professionals should equip individuals with spinal cord injury with adequate self-employment skills. Sociocultural and religious aspects should be considered in the measurement of quality of life.